DEVELOPMENT OF EFFICIENT CALCIUM OXALATE REMOVAL TECHNIQUES FROM TARO CORMS - Cahyo Kumoro, Andri (Prosiding SNST Fakultas Teknik, 2012)
Taros (Colocusiu and Xanthosoma spp.) are tropical root crops commonly referred to as cocoyams, which have been used as subsistence staple foods in many parts of the tropics and sub-tropics in Africa and Australasia. Proximate analysis of the taro corms has shown that it contains digestible starch, protein of good quality, vitamin C, thiamin, riboflavin and niacin. However, one major limiting factor in the utilization of taros is the presence of oxalates which impart acrid taste or cause irritation when foods prepared from them are eaten. Ingestion of foods containing oxalates has also been reported to cause caustic effects, irritation to the intestinal tract and absorptive poisoning as well as disrupting the bio-availability of calcium. While several methods have been made to reduce oxalate content in taro corms, none has been reported to meet the satisfactory level of the consumers. Considering that calcium oxalate content in the skin is higher than in the tuber flesh and that physical (thermal and irradiation) degradation of calcium oxalate is more pronounced than chemical and biological degradations, a method to reduce the calcium oxalate content in the taro corms is proposed. The proposed method involves peeling, washing, steeping, boiling and drying, which is expected to remove about 93.14% of the original calcium oxalate content. Keywords: taro; calcium oxalate; removal; development